The effect of age and sex on absolute volume and fractional anisotropy values of the trigeminal nerve in healthy young adults - Arruda, Eduardo Rocha; Salmon , Carlos Ernesto Garrido; Konell, Hohana Gabriela; Santos , Antonio Carlos dos (Headache Medicine, 2024)
Introduction: Some chronic orofacial pain diseases have a well-defined etiology, such as classic neuralgia of the trigeminal nerve (TN). However, in idiopathic TN neuralgia the symptoms suggest problems directly in the NT. Studies that evaluate the absolute volume (AV) in different regions of interest (ROIs) of the TN in young, healthy adults contribute to defining a standard of normality, but are scarce in the current literature and have a small number of individuals. Additionally, Diffusion Tensor Imaging (DTI) allows white matter integrity to be assessed by calculating diffusion metrics such as fractional anisotropy (FA).Purpose: To evaluate the VA in different portions of the NT of healthy young adults, and verify the effect of volume, age and sex on the TN FA values ​​in the General Linear Model (GLM).Method: Structural and diffusion MRI data from 300 healthy individuals, 150 men and 150 women, aged between 22 and 35 years, were obtained from the Human Connectome Project (HCP) database, separated into 6 groups considering age and sex. T1w images were used for bilateral marking of the ROIs: total TN, root entry zone, middle portion of the cistern and Merckel's cave. The marking of ROIs, FA maps, calculation of FA and AV of the ROIs were done using the MRTrix3 software. The results were analyzed using the Kurskal-Wallis test (p